Determination of the fatty acid and anti-oxidant vitamin profile of Nigerian rubber and palm kernel seed oils - Oriji, O.G.; Nartey, V.K.; Brimah, A.K. (International Journal of Applied Chemistry, 2015)
The rubber seed is a semi-dried substance that does not contain any unusual fatty acid but is a rich source of polyunsaturated fatty acids that make up more than 50% of its total fatty acid composition. The palm kernel oil is one of the most widely used of the lauric acid oil which contains a high level of saturated fatty acids such as lauric acid. The fruits are fleshy and elongated, egg-shaped and of a reddish colour The oils from the two seeds were extracted with hexane using the soxhlet extraction technique. These oils were later screened by determining their fatty acid and anti-oxidant vitamins by the use of GC-FID. The rubber seed oil had oleic-24.06mg/kg; linoleic-22.50mg/kg; linolenic-36.30mg/kg and palm kernel had:lauric-45.81mf/kg; myristic-18.23mg/kg; palmitic-6.94. In other words rubber seed oil was composed more of unsaturated fatty acids while the palm kernel oil was composed more of saturated fatty acids. The oils were also screened for anti-oxidant vitamins with a GC-FID, and were found to contain vitamin E and other vitamins which make them vital materials for industrial applications. © Research India Publications.
Keywords: Fatty acids; Lauric; Oleic; Rubber; Palm kernel; Vitamin